The Evolution of School Policy on failure and underachievement: the case of Canton Ticino - Dozio, Edo (Swiss Journal of Educational Research, 2001)
The article traces the evolution of educational policy on school failure and underachievement due to different causes in Canton Ticino during the last 50 years: period when the area underwent important demographic and economic change. The educational system chosen was headed by the concept of integration and this has had radical effects on the organization of the lower secondary school. The democratization of education has changed the relationship between society and school and the reform of special educational needs and the setting up of a service of pedagogical help ( Servizio di sostegno pedagogico ) led to a new perception of what differences in learning ability and failure in school could mean. During the last 30 years the available special services have been reinforced and the concepts and practice dealing with underachievement have undergone constant revision. However, the need for further change can be perceived.